Progress on the Fifteenth General Review of Quotas-Report of the Executive Board to the Board of Governors (April 2018). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
Following the guidance on the Board of Governors Resolution No. 72-1 (December 2016), on April 3, 2018, the Executive Board discussed and adopted its second semi-annual report on progress on the Fifteenth Review. The report covered issues relating to both the adequacy of Fund resources and the quota formula and realigning quota shares, discussed in an informal meeting on February 2, 2018 and building on the earlier discussions in the fall of 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Directors Noting; Financial Crises; PP; Quota Share; Resource Composition